Investigation Of Wear And Corrosion Characteristics Of Short Heat Treated Thixoformed Aluminium Alloy - Salleh, Mohd Shukor; Abd Rahman, Ammar; Othman, Intan Sharhida; Subramonian, Sivarao; Yahaya, Saifudin Hafiz; Siswanto, Nurhadi (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
The thixoformed Al-Si-Cu alloys play an important role in automotive and engineering industries due to their wear resistance properties. This investigation looks into the wear and corrosion behaviors of thixoformed Al-Si-Cu alloy. Attempt has been made to relate the coefficient of friction (CoF) and corrosion rate on the short series of T6-heat treatment of thixoformed LM4 aluminium alloy. The short T6 heat treatment involves the application of solute solutioning, quenching and artificial ageing. Dry sliding condition using a pin-on-disc configuration against the SKD II steel disk under a constant load, distance and speed of 10 N, 1000 m and 0.1 m/s respectively was conducted to investigate the wear. The CoF of thixoformed shows an improvement of 5% where the T6 treated alloy is 0.4299 as compared to the 0.4537 untreated LM4 alloy. Furthermore, a significant reduction of 54% from 2.5459x10-4 mmpy to 1.1697x10-4 mmpy corrosion rate was also noted between the untreated and treated thixoformed alloy. Therefore, the alloys that undergone the short T6 heat treatment cycle generally improved the wear and corrosion resistant as compared to the alloys without heat treatment.